Cancer Survival Experiences Retold Through Web Portal - Kok, Yew Ang; Ah , Choo Koo; Yan, Peng Lim (2016)

(untitled)
The purpose of this paper is to examine the experience of cancer survivors while they are still a patient of cancer. Their reflections were documented in video form and published via a web portal entitled ‘Share’. Besides that, this paper also seeks to understand the impact of experience retold via the portal to media users who are generally the support group members. This research uses a qualitative approach which involved five cancer survivors for the actual interviews while two cancer survivors for pilot interviews. The researcher conducted in-depth interviews with empathetic listening approach in order to collect the cancer survivor’s experience. Maslow’s Theory of Motivation is adopted as a conceptual framework for guiding the research particularly in framing the interview questions that focuses on exploring the physiological, safety, love and belonging needs of cancer survivors which is the first three levels discussed in Maslow’s theory. A survey is disseminated to the support group to understand their perception towards the Share’s portal. The results informed that the cancer survivors needs have been identified accordingly to the first three levels of Maslow’s theory. The cancer survivors’ needs were similar to each other when they were still patients. Their sharing intention was high, because they had reached a certain level of attitude compared to the time when they are healthy after experiencing a bigger challenge in their lives. As for the feedbacks from the support group majority of the feedbacks support the role of this portal to keep them connected and agreed on the importance to have such a portal to cater to their support group. This study enables the researcher to understand the experience sharing process and learning from the cancer survivors. Besides that, this study offers a better understanding of the needs of cancer patients. This study benefits the cancer support group in Malaysia because of the fundamental needs for the cancer support group to enable them to have a better knowledge, experiences, and advice sharing to new cancer patients. Such information offers the community a better understanding of the needs of cancer patients based on Maslow’s Theory of Needs. Maslow’s Theory is widely used in the healthcare and hospice study in the recent years